An investigation of the level of burnout and resilience among hospital based nurse managers after COVID 19 — A cross‐sectional questionnaire‐based study. (6th November 2022) - Pallesen, Kirsten Siig; McCormack, Brendan; Kjerholt, Mette; Borre, Line Zacho; Rosted, Elizabeth; Hølge‐Hazelton, Bibi
Abstract: Aim: We aim to investigate burnout and resilience among hospital based nurse managers post COVID‐19 in order to suggest appropriate person‐centred leadership support. Background: Nurse leaders are central to establishing safe and caring environments for patients and staff. Therefore, their own wellbeing is crucial, particular in times of crisis where they must provide support and guidance. Methods: Cross‐sectional questionnaire included ward managers. Data collected were burnout inventory, brief resilience score and demographic data. To analyse data, we used descriptive statistics. Results: 51.2% answered the questionnaire. Of those, 32.3% displayed symptoms of high personal burnout and 29% of work‐related burnout. 6.5% showed signs of high employee‐related burnout. As a group, ward managers showed moderate to high resilience. Conclusion: Personal and work‐related burnout was highly prevalent among ward managers. Results suggest that the cause of their burnout symptoms cannot be attributed to low individual resilience. We thus suggest a shift in focus from strengthening individual leadership resilience to the establishment of healthful and resilient cultures in accordance with person‐centred leadership. Implications for Nursing Management: Person‐centred leadership has the potential to shift the focus from the resilience of individual leaders to that of collective responsibility for creating a healthful and resilient culture.